PENGEMBANGAN JALUR EVAKUASI DI DESTINASI WISATA PANTAI RAWAN TSUNAMI UNTUK KETAHANAN BENCANA - Soviana, Widya; Mubarak, Zakiyul; Wibowo, Kiki Dedi; Fatimah, Aldina; Munawir (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
Coastal tourist destinations located in tsunami-prone areas exhibit high vulnerability to disasters, particularly given the number of tourists unfamiliar with local hazards and evacuation procedures. This study aims to develop effective evacuation routes in coastal tourist areas to mitigate the risk of casualties and losses due to tsunamis. The method used in this research is a case study with a spatial analysis approach, where existing evacuation routes are evaluated based on accessibility, travel time, and safety for tourists. Data were collected through field surveys, interviews with local stakeholders, and simulation-based evacuation modeling. The results show that there are six evacuation routes leading to vertical evacuation shelters on Lampuuk, Lhoknga, with two of the routes exceeding the safe evacuation time limit. The current evacuation routes are insufficient due to a lack of signage, routes that are not easily accessible for tourists, and reliance on vulnerable infrastructure. Therefore, new evacuation routes need to be developed, taking into account evacuation distance, topography, visitor behavior, and local community participation in the planning process to strengthen the resilience of tourist destinations against tsunami threats.